Diversification of International Student Base: A Misplaced Effort - Liu, Wei (Journal of International Students, 2021)
Underlying the goal of diversifying the sources of international students in post-secondary education is a naive logic: The portfolio of international students is controlled by the recruitment efforts of host countries and universities. Given this logic, the host countries and universities decide on where their international students are from and how diverse their international student population is. The logic results in an overestimate of the value of recruitment efforts by host countries and universities. It tends to overlook a whole range of other macro factors that determine international student mobility more significantly than recruitment efforts. Most notably, certain macro factors are beyond the control of host countries and universities, and their diversification efforts are futile and a waste of resources.